The Impact of Cultural Diversity Management on Employee Satisfaction and Organizational Commitment in Higher Education - Lamin SaidyJeng (Airlangga Journal of Innovation Management, 2026)
Cultural diversity has become a defining feature of contemporary higher education institutions, yet the effectiveness of diversity management in developing countries remains insufficiently examined. This study investigates how cultural diversity is perceived and managed at the University of The Gambia, examining relationships between diversity perceptions and employee outcomes. Using a quantitative research design, primary data were collected through a structured survey administered to 151 academic and administrative staff. Data was analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. Findings indicate that 78.8% of respondents recognize the University of The Gambia as culturally diverse, and 83.4% feel comfortable in cross-cultural interactions. However, only 51.0% agree that performance evaluations are conducted fairly. Correlation analysis revealed significant relationships between diversity management perceptions and job satisfaction (r = .423, p < .01), and between leadership commitment and perceived fairness (r = .512, p < .01). Regression analysis identified leadership commitment as the strongest predictor of perceived fairness (β = .312, p < .001). The study concludes that effective diversity management requires stronger alignment between institutional policies, leadership practices, and transparent procedures. Future research should employ qualitative methods to explore experiences underlying neutral responses and conduct comparative studies across multiple institutions. The findings suggest universities should strengthen leadership capacity for inclusive management and enhance transparency in evaluation and recognition processes.